Improving the Well-Being of Adolescent Girls in Developing Countries - World Bank (World Bank, Washington, DC, 2022)
Adolescent girls are viewed as a key demographic group to target for successfully breaking the intergenerational transmission of poverty in developing countries. Unfortunately, for many teenage girls in developing countries, adolescence entails a fleeting transition from childhood to adulthood, when they are expected to behave as adults even though they are not biologically, cognitively, or emotionally ready to assume adult responsibilities. This report summarizes the state of the evidence and provides policy guidance on interventions that have sought to: (1) increase educational attainment; (2) delay childbearing; and/or (3) delay marriage for adolescent girls in developing countries. The focus is on these three outcomes because it is believed that altering these outcomes can have lasting effects on an individual’s well-being as well as the well-being of others, for example an individual’s (future) children. Despite these outcomes having long-lasting effects on lifetime well-being, they can be readily measured in the short-medium term, making it easier for researchers to analyze the impacts of different interventions on them.